Moving to Open Educational Resources at Athabasca University: A Case Study - Ives, Cindy; Pringle, Mary Margaret (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2013)
Since the birth of the World Wide Web, educators have been exchanging ideas and sharing resources online. They are all aware of the turmoil in higher education created by freely available content, including some hopeful developments charted in this issue. Interest has grown steadily over the past decade in making a university-level education openly available to students around the globe who would otherwise be overlooked, and recommendations for how to do this are well documented (e.g., UNESCO, 2002; OECD, 2007). Initiatives in the United States (Thille, 2012), Canada (Stacey, 2011b), Africa (OER Africa, n.d.), and the United Kingdom (JISC, 2012) are easily accessed and case studies abound (e.g., Barrett, Grover, Janowski, van Lavieren, Ojo, & Schmidt, 2009). Supporting the widespread availability of OER is a goal that Athabasca University (AU) has embraced through association with the Commonwealth of Learning and by becoming a charter member of the OER University (OERu, 2011). The use of OER in AU programs has strategic local implications that go beyond the five reasons for institutions to engage in OER projects described by Hylén (2006). Recently at AU explorations have begun into the potential of using OER in course design and production.